Single institution retrospective review of perioperative chemotherapy in adult and adolescent patients with operable osteosarcoma. Issue 2 (20th February 2014) - Hansen, Aaron R; Hughes, Brett GM; Paul, Sanjoy; Steadman, Peter; Sommerville, Scott; Dickinson, Ian C; Walpole, Euan T; Thomson, Damien B; Mar Fan, Helen G; Joubert, Warren L
Abstract: Aims: Perioperative chemotherapy has improved the prognosis for patients with operable osteosarcoma. The literature is conflicting about which regimen is optimal. The aim of this study was to evaluate the survival outcomes of two cohorts of patients with operable osteosarcoma treated with different perioperative chemotherapy regimens. Methods: This was a retrospective review of patients diagnosed with operable osteosarcoma treated at the Princess Alexandra Hospital from 1986 to 2009. The standard perioperative chemotherapy regimen changed from the modified T10 Rosen protocol to cisplatin/doxorubicin in 1997. Using the Kaplan–Meier method, overall survival (OS) and disease‐free survival (DFS) curves were generated for the cisplatin/doxorubicin and the modified T10 Rosen cohorts. Results: Seventy‐one patients were identified of whom 63 had potentially curable disease. Of these, 24 received the modified T10 Rosen regimen and 39 received cisplatin/doxorubicin. There was a non‐significant trend toward better OS and DFS in the patients who received the modified T10 Rosen protocol. Conclusion: The trend toward poorer survival in the cisplatin/doxorubicin cohort, in combination with current evidence, has prompted our institution to change its practice.